Difficulties on the determination of the flammability limits of fuel mixtures by the Law of Le Chatelier - Mendiburu, Andrés Z.; Coronado, Christian R.; de Carvalho, João A. [UNESP] (Elsevier, 2020)
In the present article the inaccuracies related to the estimation of the upper flammability limits of fuel mixtures in air by using the Law of Le Chatelier are analyzed. A derivation of the Law of Le Chatelier was provided in order to understand the necessary conditions for its applicability. A statistical analysis was applied to the available experimental data for the lower and upper flammability limit of fuel mixtures. It was observed that the direction of flame propagation has a significant effect on the inaccuracies. The fuel mixtures for which the absolute values of the relative errors were higher than 10 % were selected for further study. Through the determination of the laminar flame speeds it was shown that those deviations were related to different heat release rates at the experimental and calculated upper flammability limits, respectively. A laminar flame speed sensitivity analysis was also applied to a selected group of fuel mixtures and two competing reactions for each mixture at the upper flammability limit were identified.
Keywords: Derivation; Flammability limits; Law of Le Chatelier; Validation